Biogeographic analysis and key to the genera of ferns and lycophytes of Mburucuyá National Park, Corrientes, Argentina - Meza Torres, Esteban I. (2013)
The diversity of ferns and lycophytes of Corrientes province, Argentina is not well understood. Our field work in the Mburucuyá National Park in Corrientes province as well as a literature review fi nds 29 genera and 48 infrageneric taxa of ferns and lycophytes for this Park. A comparison of the Park's species diversity with other protected areas in northeastern Argentina using Jaccard's similarity coeffi cient and the infrageneric taxa biodiversity index proposed by Squeo et al. (1998) are analized. A key to the Park's ferns and lycophytes genera is provided.